Recovery Process of Condensate the Ammonia Wastewater Plant of PT.PIM with A Combination of Technology Air Stripping Jet Bubble Colum, Advance Oxidation process and Ion Exchange Resin - Muhammad Nur; Edi Munawar; Mariana Mariana (Jurnal Rekayasa Kimia & Lingkungan)
Abstract